Factors Associated with Nurse Compliance in the Application of Standard Precautions to Infection Prevention - Yotlely, Abraham Steven; Fitryasari, Riski; Mishbahatul M.Has, Eka (Universitas Airlangga, 2019)
Introduction: Standard precaution to prevent infection is applied in patient treatment in the health service facility to prevent the cross of infection has established prior to patient diagnosis, laboratory examination, and after patient diagnosis. The aim of this research was to analyze some factors related to nursing compliance in the application of standard precaution in the X Regional Public Hospital.Method: Research used correlational design by using the cross-sectional method. The populations of this research were all nurses who worked in the UGD and the X hospital treatment room. The samples were used 90 respondents of 116 nurses who were sampled by using stratified random sampling. The dependent variable was nursing compliance. Meanwhile, the independent variables were an individual factor (knowledge and perception of risk), occupational factor (resistance of standard precaution application and workload), and organizational factor (safety climate, information and training, and facility availability). Instruments used questioner and observation. Then they were analyzed by using logistic regression test with significant rate <0.05.Result: There was a significant relationship between knowledge (0=0.014), information and training (p=0.023) with nurse compliance in the application of Standard Precautions.Conclusion: The increase of knowledge, information, and training effect to nurse compliance in the application of standard precautions, so it is needed management support in increasing knowledge, information, and training about standard precautions.